Preliminary study on the aerodynamics of parafoils - Song, Yifan (2016)
This project presents a basic wind tunnel investigation on aerodynamics of ram-air parafoils. Previous studies are summarized through detailed literature reviews, and key parameters for a generic parafoil such as airfoil shape, inlet opening cut, arc-anhedral angle, chord and aspect ratio, and cells are identified. A model support mechanism coupled with a 6-component load cell balance system is designed and validated. The aerodynamic characteristics of five ram-air parafoil models at airspeed of 20 m/s, 30 m/s and 40 m/s are obtained by conducting low speed wind tunnel tests in Temasek Lab, NUS. Some necessary flow visualization studies are also performed. Results of the investigations show the inlet opening cut has fewer effects on aerodynamic coefficients. The arc-anhedral wing is able to reduce flow separation from center to wing tip along the span. The troughs on canopy caused by inflation can also weaken the flow separation. With a flap deflection of 12 degrees, an efficiency of about 122% in lift generation and an increase of about 0.61 in coefficient of Uft are found.